Comparative thermoeconomic and thermodynamic analyses and optimization of an innovative solar-driven trigeneration system with carbon dioxide and nitrous oxide working fluids. (January 2022) - Cao, Yan; Dhahad, Hayder A.; Sharma, Kamal; ABo-Khalil, Ahmed G.; El-Shafay, A.S.; Ibrahim, Banar Fareed
Abstract: Solar energy is pollution-free and causes no greenhouse gas emissions after installation and during power generation. Regarding the environmental concerns raised by power generation systems, in the present study a novel solar-based CCHP system is proposed. The system is a modified configuration of conventional Rankine cycle and ejector refrigeration cycle, integrated in such a way that it can operate on complete CHP or CCP modes by regulating the extracted mass flow ratio from the power turbine. An additional remarkable feature of the proposed system is the usage of environmental-friendly working fluids: CO2 and N2 O. To enhance the proposed system performance booster compressor is employed in refrigeration loop to increase the cooling production and a thermoelectric generator is used to recover some part of the cycle waste heat. Feasibility analysis and multi-objective thermoeconomic optimizations are conducted to evaluate the system performance. Also, to achieve more practical results, actual data for a real case study are considered and the annually performance of the system is assessed. The superiority of N2 O compared to CO2 is revealed in terms of power and efficiency, as well as Levelized Cost of Electricity (LCOE). Also, the solar sub-section (collector field + TES) has the highest value of exergy destruction, which is more than 76% of overall system destructions. Under the optimal operation, thermal efficiency and LCOP values, respectively are 40.32% and 15.32 $/GJ for N2 O working fluid. Also, the monthly performance investigation indicated the best and worst performance for the proposed system on May and December, respectively. Highlights: Proposal of an innovative CCHP system based on TRCC cycle driven by solar energy. Employing booster compressor and thermoelectric generators to enhance system performance. Adjustable power, cooling and heating outputs from the system to satisfy user energy demand. Considering actual data for a real case study and evaluation of the system monthly performance. Using N2O as the working media in the proposed system and performance comparison with CO2.